Four new caponiids species (Araneae, Caponiidae) from the West Indies and redescription of Nops blandus (Bryant) - Sánchez–Ruiz, Alexander; Brescovit, Antonio D.; Alayón, Giraldo (Zootaxa, 2015)
We update the knowledge of the unusual Caponiidae spiders from the West Indies with the description of four new species, and the redescription of Nops blandus (Bryant) including the first description of the female. Specimens previously assigned to N. blandus from Hispaniola and Puerto Rico represents two new species: Nops hispaniola n. sp. and Nops agnarssoni n. sp. respectively; while the distribution of the former is limited to British and U. S. Virgin Islands. The others two new species are Nops finisfurvus n. sp. from British Virgin Islands and Cubanops luquillo n. sp. from Puerto Rico. Female internal genitalia of Nops species are described, photographed and illustrated for the first time.